Lars Levi Laestadius' attitude to Saami religion - Hallencreutz, Carl (Scripta Instituti Donneriani Aboensis, 1987)
How Læstadianism became the "religion of the Saamis" is a process of church and religious history which has not been fully explained. It is a comprehensive development which includes most of Læstadius' entire ministry. In this work he did not regard the Saami religion as something exclusively out of date. Instead, he put his message in a more concrete form by making use of Saami ideas. A central question is how Læstadius took account of—or afforded expression to motives from traditional Saami mythology when he formulated and adapted his own interpretation of Christianity to the Saami environment. For instance, the existence of the mother goddess (Madder-akka) and other female deities was something extremely concrete in Saami pre-Christian. In Læstadius' time conceptions and the worship of these deities had ceased. Despite this, Læstadius may have found it of value, in a living Saami interpretation of Christianity, to give a more rounded picture of the deity that was expressed in Christian usage by the old Saami god of thunder and sky, Jubmela by keeping alive the mother aspect of "the heavenly parent". Therefore he may have consciously chosen to use mother symbolism when talking of the secret of atonement.